2014
DOI: 10.1128/jb.00028-14
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Streptococcal Membrane Protein, LsrS, Exhibits a Receptor-Like Function for Lantibiotics

Abstract: Streptococcus mutans strain GS-5 produces a two-peptide lantibiotic, Smb, which displays inhibitory activity against a broad spectrum of bacteria, including other streptococci. For inhibition, lantibiotics must recognize specific receptor molecules present on the sensitive bacterial cells. However, so far no such receptor proteins have been identified for any lantibiotics. In this study, using a powerful transposon mutagenesis approach, we have identified in Streptococcus pyogenes a gene that exhibits a recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 77 publications
0
12
0
Order By: Relevance
“…To test this, we performed subcellular fractionation experiments on S. intermedius B196 (Si B196 ) cells expressing vesicular stomatitis virus glycoprotein G (VSV-G) epitope-tagged TipC (TipC-V). The characterized streptococcal proteins manganese-dependent superoxide dismutase (SodA) and l antibiotic S mb r eceptor-like function in s treptococci (LsrS) were used as cytoplasmic and membrane protein fractionation controls, respectively [15] , [16] . Consistent with our hypothesis, we found that TipC localizes to the membrane fraction ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To test this, we performed subcellular fractionation experiments on S. intermedius B196 (Si B196 ) cells expressing vesicular stomatitis virus glycoprotein G (VSV-G) epitope-tagged TipC (TipC-V). The characterized streptococcal proteins manganese-dependent superoxide dismutase (SodA) and l antibiotic S mb r eceptor-like function in s treptococci (LsrS) were used as cytoplasmic and membrane protein fractionation controls, respectively [15] , [16] . Consistent with our hypothesis, we found that TipC localizes to the membrane fraction ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The role of AyrA, which encodes a membrane protein of unknown function, is even less clear, but it is interesting to speculate that it could be a protease responsible for intramembrane cleavage, if one is required, which is consistent with its predicted membrane localization. It is also interesting that ayrR homologs in other species appear to control the regulation of proteases ( 25 , 26 ). A more complete understanding of the pathway awaits detailed analysis of these proteins as well as the signal responsible for derepression of the operon, which is in progress.…”
Section: Observationmentioning
confidence: 99%
“…In addition, it is believed that lantibiotics most probably recognize a specific receptor molecule on sensitive bacterial cells. To date, however, only one receptor-like protein has been discovered, with the identification in Streptococcus pyogenes of a gene encoding a protein named LsrS, which exhibits a receptor-like function for the lantibiotic Smb (10). LsrS is a membrane protein that belongs to the CAAX protease family and is well conserved across streptococcal species.…”
Section: Mode Of Actionmentioning
confidence: 99%